Cornmeal-based artificial diet improves development and reduces rearing costs of Spodoptera litura - Fan, Aning; Huang, Yibo; Kanjana, Nipapan; Wang, Hanzhang; Mao, Jianjun; Li, Yuyan; Zhang, Junjie; Zhang, Lisheng (Frontiers in Insect Science, 2025)
The tobacco cutworm, Spodoptera litura (Fabricius) (Lepidoptera: Noctuidae), is a major defoliating pest in East and South Asia and serves as an alternative host for the mass propagation of the parasitoid Telenomus remus. Therefore, optimizing the rearing cost of S. litura is critical for large-scale production to enhance efficiency and reduce costs. We evaluated 18 artificial diet formulations derived from a standard diet by incorporating corn flour and adjusting the ingredient ratios. The diets were grouped into high-, medium-, and low-cost categories, and their biological performance was assessed under controlled laboratory conditions (26 ± 1 °C, 70 ± 5% RH, and a16:8 h L:D photoperiod). Among the tested diets, formulation 15 produced the best results, yielding shorter larval (19.52 d) and pupal durations (10.46 d), higher pupal mass (500 mg), greater fecundity (2,658 eggs/female), and improved egg hatch (73.77%) compared with the control. Population parameters, including the intrinsic (r) and finite (λ) rates of increase, were significantly improved, whereas the mean generation time (T) and net reproductive rate (R0) decreased. Importantly, formulation 15 lowered rearing costs by 5.9% relative to the original diet. These findings demonstrate that replacing soybean flour with corn flour as the primary protein source provides a cost-effective and biologically robust diet for S. litura. This optimized diet will facilitate large-scale rearing of S. litura and mechanized production of T. remus, providing a model for reducing artificial diet costs in other insect systems.